2015
DOI: 10.1038/nclimate2513
|View full text |Cite
|
Sign up to set email alerts
|

Unabated planetary warming and its ocean structure since 2006

Abstract: Increasing heat content of the global ocean dominates the energy imbalance in the climate system 1 . Here we show that ocean heat gain over the 0-2,000 m layer continued at a rate of 0.4-0.6 W m −2 during 2006-2013. The depth dependence and spatial structure of temperature changes are described on the basis of the Argo Program's 2 accurate and spatially homogeneous data set, through comparison of three Argo-only analyses. Heat gain was divided equally between upper ocean, 0-500 m and 500-2,000 m components. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
450
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(491 citation statements)
references
References 38 publications
38
450
3
Order By: Relevance
“…1-from [72]). As expected, the global warming rate shows its strongest magnitude in the first few hundred meters of the water column and the interannual variability above 500 m shows pronounced changes that control the global temperature variations at the air-sea interface [60]. Those upper OHC changes reflects in large part the ElNiño/Southern Oscillation (ENSO) and its influence on the horizontal tilt of the equatorial thermocline in the Pacific.…”
Section: The Unabated Heating Of the Upper Ocean The Global Picture Dsupporting
confidence: 52%
“…1-from [72]). As expected, the global warming rate shows its strongest magnitude in the first few hundred meters of the water column and the interannual variability above 500 m shows pronounced changes that control the global temperature variations at the air-sea interface [60]. Those upper OHC changes reflects in large part the ElNiño/Southern Oscillation (ENSO) and its influence on the horizontal tilt of the equatorial thermocline in the Pacific.…”
Section: The Unabated Heating Of the Upper Ocean The Global Picture Dsupporting
confidence: 52%
“…This larger ratio raises concern about the use of the model results for adjusting the observational estimates, as suggested by Durack et al [61]. One of the mapping techniques used in Roemmich et al [63] also directly addressed the mapping deficiencies in the tropical Asian archipelago identified in von Schuckmann et al [58] [64] demonstrated agreement between regional ocean-mass trends determined from GRACE data and the difference between altimeter sea level observations and ocean steric sea level change.…”
Section: Sea Level Contributions Steric Sea Level Changementioning
confidence: 97%
“…In contrast, the observational estimates ranged from about 35 [62] to about 50 % [49], suggesting that historical ocean heat content estimates may be biased low by various amounts because of lack of data in the Southern Hemisphere. Based on Argo data from 2006 to 2014, Roemmich et al [63] found an even larger ratio of Southern to Northern Hemisphere ocean heat uptake (67 to 98 %) possibly as a result of greater negative aerosol forcing in the Northern Hemisphere and/or ocean heat uptake processes. This larger ratio raises concern about the use of the model results for adjusting the observational estimates, as suggested by Durack et al [61].…”
Section: Sea Level Contributions Steric Sea Level Changementioning
confidence: 99%
“…Continued use of fossil fuels into the 21st century is predicted to lead to atmospheric CO 2 levels > 900 ppm by 2100 (under Representative Concentration Pathway (RCP) 8.5; Meinshausen et al, 2011), though the precise level is highly dependent on the emission scenario (Pachauri et al, 2014). These rising atmospheric greenhouse gas concentrations have led to an increase in global average temperatures of ~ 0.2°C decade -1 , much of which has been absorbed by the oceans, whilst the oceanic uptake of atmospheric CO 2 has led to major changes in surface ocean pH (Levitus et al, 2000(Levitus et al, , 2005Feely et al, 2008;Hoegh-Guldberg and Bruno, 2010;Mora et al, 2013;Roemmich et al, 2015). The deep sea has experienced dramatic changes in physical and chemical variables in the geological past.…”
Section: Introductionmentioning
confidence: 99%